Prevalence of Methicillin-Resistant Staphylococcus aureus and Associated Risk Factors among Patients with Wound Infection at Referral Hospital, Northeast Ethiopia. (26th May 2020) - Tsige, Yeterefwork; Tadesse, Senait; G/Eyesus, Tsehaynesh; Tefera, Mulugeta Mihrete; Amsalu, Anteneh; Menberu, Marta Alemayhu; Gelaw, Baye
Abstract : Background. The spectrums of infections due to methicillin-resistant Staphylococcus aureus are manifold and are associated with worse outcomes. A study on the prevalence of these pathogens and their sensitivity patterns will give updated information which is very helpful for health personnel responsible in the management of patients and timely monitoring of the emergence of resistant bacteria. Hence, the study aimed at assessing the prevalence of methicillin-resistant Staphylococcus aureus and associated factors among patients with wound infection at Dessie Referral Hospital. Method . A cross-sectional study was conducted among 266 patients at Dessie Referral Hospital from February to May 2016. Wound swab samples were collected aseptically using Levine's technique and transported to Dessie Regional Laboratory by using brain-heart infusion transport media. Isolation of Staphylococcus aureus was done based on cultural and biochemical profiles. Drug susceptibility test was performed using the disc diffusion technique as per the standard and interpreted based on the Clinical and Laboratory Standards Institute guidelines. The data were entered and analyzed by using SPSS version 20. Result . Staphylococcus isolates from 266 processed wound swabs were 92 (34.58%). Of these, 26 (28.3%) were identified as methicillin-resistant S. aureus and 66 (71.7%) were methicillin-sensitive S. aureus . The overall prevalence of methicillin-resistant S. aureus among the study population was 9.8%. The isolated methicillin-resistant S. aureus showed full resistance to penicillin (100%) followed by erythromycin and ciprofloxacin (16, 61.5%) and cotrimoxazole and gentamicin (14, 53.8%). From the total S. aureus isolates, 20 (21.7%) of them showed multidrug resistance. Of these methicillin-resistant S. aureus, 18 (69.8%) showed high multidrug resistance. Patients who are farmers in occupation (AOR = 6.1, 95% CI (1.086–33.724)), admitted in the hospital (AOR = 3.56, 95% CI (1.429–8.857)), and have low BMI (<18.5) (AOR = 13.89, 95% CI (4.919–39.192)) were among the risk factors significantly associated with wound infection due to methicillin-resistant S. aureus . Conclusion . All methicillin-resistant S. aureus isolates were 100% resistant to penicillin and showed high multidrug resistance. Therefore, antibiotic susceptibility test should be performed prior to treatment.